Incompetence of Vector Capacity of Rhipicephalus bursa to Transmit Babesia aktasi following Feeding on Clinically Infected Goat with High Level of Parasitemia - Ulucesme, Mehmet Can; Ozubek, Sezayi; Aktas, Munir (Mdpi, 2024)
The tick species involved in the transmission of Babesia aktasi, which is widespread in the Mediterranean region, is unknown. However, studies have shown that Rhipicephalus bursa is the most common tick species in the regions where the prevalence of B. aktasi is widespread. This finding increases the possibility that R. bursa may serve as a vector for the transmission of B. aktasi and encourages the evaluation of the vector competence of R. bursa. For this purpose, clinical babesiosis was induced in an immune-suppressed indigenous donor goat. Babesia spp.-free R. bursa larvae (n = 2000) and adults (n = 25) obtained from laboratory colonies fed on the donor goat. Following oviposition, PCR analysis of engorged female carcasses and engorged nymphs revealed the presence of B. aktasi, whereas no positivity was found in unfed larvae and adult ticks. The subsequent developmental stages of these ticks were used to infest three additional immune-suppressed goats. No clinical signs of babesiosis were observed in the infested goats. Moreover, molecular analysis did not detect DNA in the goats. These results demonstrated that R. bursa does not transmit B. aktasi, neither transovarially nor transstadially. A recent molecular survey revealed a high prevalence of Babesia aktasi in indigenous goats from the Mediterranean region of T & uuml;rkiye, coinciding with heavy Rhipicephalus bursa infestations. This geographical overlap has raised the possibility that R. bursa may serve as a vector for the parasite. To evaluate the potential of R. bursa to serve as a vector for the parasite, an experimental study was conducted in indigenous goats. An immune-suppressed donor goat was intravenously injected with 15 mL of the cryopreserved B. aktasi stabilate, resulting in severe clinical babesiosis and parasitemia. Subsequently, R. bursa larvae and adults derived from Babesia-free laboratory colonies were allowed to feed on the infected donor goat. After oviposition, engorged female carcasses, representative engorged nymphs, unfed larvae, and adult pools were used for DNA extraction and PCR analysis. No PCR positivity was detected in any of the DNA samples, except for those with engorged female carcasses and nymphs. Three immune-suppressed recipient goats were infested with the unfed immature and mature ticks consuming the blood of a donor infected with B. aktasi. No clinical or parasitological findings were encountered in the recipient for 40 days post-infestation. These findings indicated that R. bursa was not a competent vector for B. aktasi.
Keywords: Babesia aktasi; experimental study; Rhipicephalus bursa; transstadial and transovarial transmissions; vector competence